1988
DOI: 10.1007/bf01686355
|View full text |Cite
|
Sign up to set email alerts
|

The role of returns to a prior topic in the negotiation of topic change: A developmental investigation

Abstract: Returns to a prior topic occurring in the conversations of small groups of acquainted peers were examined to learn more about how topic is organized in such settings and how it changes with age. Twenty-five discussion groups were formed, five at each of the following grades: second, fifth, ninth, twelfth, and college. The eighth meeting of each group was examined, comprising 13,811 speaking turns total, which includes 502 returns other than those occurring after side sequences. There are three main findings. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Over half of the group process metatalk involved this type of discourse, suggesting that Ms. Johnson's group had difficulty interacting with one another. These findings are consistent with those of Sirois and Dorval (1988) who noted that less proficient discussants engaged in more topic fights and were less adept at negotiating topics. Ms. Evans's more proficient group had 14 episodes of group process metatalk (see Table 5).…”
Section: Billysupporting
confidence: 90%
See 4 more Smart Citations
“…Over half of the group process metatalk involved this type of discourse, suggesting that Ms. Johnson's group had difficulty interacting with one another. These findings are consistent with those of Sirois and Dorval (1988) who noted that less proficient discussants engaged in more topic fights and were less adept at negotiating topics. Ms. Evans's more proficient group had 14 episodes of group process metatalk (see Table 5).…”
Section: Billysupporting
confidence: 90%
“…Overall, they concluded that topic coherence ability increases developmentally with age. Sirois and Dorval (1988) found similar results in their developmental study of children in Grades 2, 5, 9, and 12, and adults. Regarding topic maintenance they found substantive differences in stability of topic occurring around Grade 5.…”
Section: Developmental Issuessupporting
confidence: 68%
See 3 more Smart Citations